2020
DOI: 10.3390/ijms21217903
|View full text |Cite
|
Sign up to set email alerts
|

The Microenvironment of Decellularized Extracellular Matrix from Heart Failure Myocardium Alters the Balance between Angiogenic and Fibrotic Signals from Stromal Primitive Cells

Abstract: Cardiac adverse remodeling is characterized by biological changes that affect the composition and architecture of the extracellular matrix (ECM). The consequently disrupted signaling can interfere with the balance between cardiogenic and pro-fibrotic phenotype of resident cardiac stromal primitive cells (CPCs). The latter are important players in cardiac homeostasis and can be exploited as therapeutic cells in regenerative medicine. Our aim was to compare the effects of human decellularized native ECM from nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…In fact, previous studies showed that CSCs can exert beneficial effects in the injured myocardium, mostly by positive microenvironmental conditioning through paracrine factors, which are able to render activated fibroblasts anti-fibrotic, and to polarize macrophages towards M2-like anti-inflammatory features [ 24 , 26 , 55 58 ]. Moreover, CSC phenotype can shift from cardioprotective features towards a pro-inflammatory and pro-fibrotic behaviour in response to different cues [ 29 , 33 , 59 , 60 ]. This phenotypic shift within the heterogeneous stromal population may significantly affect adaptation and therapeutic mechanisms in response to stress and injury [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, previous studies showed that CSCs can exert beneficial effects in the injured myocardium, mostly by positive microenvironmental conditioning through paracrine factors, which are able to render activated fibroblasts anti-fibrotic, and to polarize macrophages towards M2-like anti-inflammatory features [ 24 , 26 , 55 58 ]. Moreover, CSC phenotype can shift from cardioprotective features towards a pro-inflammatory and pro-fibrotic behaviour in response to different cues [ 29 , 33 , 59 , 60 ]. This phenotypic shift within the heterogeneous stromal population may significantly affect adaptation and therapeutic mechanisms in response to stress and injury [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…These benefits on tissue repair, however, depend on specific features of CSCs. In fact, myocardial remodelling and cardiovascular risk factors, such as diabetes [ 28 ], may lead to pro-fibrotic polarization and loss of the reparative potential of CSCs [ 29 , 30 ], with impaired paracrine potency [ 31 – 33 ]. Overall, the health status, comorbidities, and ongoing therapies of a patient can strongly affect the phenotype of CSCs [ 30 32 , 34 ], and in this way their direct and indirect contribution to fibrosis and remodelling.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a so-called healthy diet plays a key role in both, primary and secondary cardiovascular prevention, and is given a class I recommendation in current guidelines [ 5 ]. Further, unhealthy diet patterns may have pro-inflammatory properties with the risk of the development and aggravation of inflammatory diseases including pulmonary infections [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sustained MMP activation will lead to extracellular matrix remodeling. Fifth, ROS mediate growth responses in ventricular myocytes by stimulating the activity of several growth factors including transforming growth factor-β1 (TGF-β1), [223,224] VEGF, [225] fibroblast growth factor-2 (FGF-2), [226], and PDGF [227]. Sixth, oxidative stress promotes vasoconstriction by increasing the production of endothelin-1 [228] and angiotensin II by increased production of 02-via the NADPH oxidase [229].…”
Section: Oxydative Stressmentioning
confidence: 99%